The Effect of Road Damage on Road User Satisfaction (Case Study: Southern Ring Road, Tuban Regency) - Domas Kurnia Atmaja; Inge Anggitasari; Monica Dewi; Olvi Pamadya Utaya Kusuma (Green Publisher Indonesia, 2025)
This study aims to analyze the effect of road damage levels on user satisfaction along the Ring Road / Southern Bypass in Tuban Regency. Poor road conditions—such as cracks, potholes, uneven patches, water puddles, and corrugated surfaces—can reduce comfort, safety, and travel speed. A quantitative approach was employed using a questionnaire containing ten statements: five measuring perceptions of road damage (variable X) and five measuring user satisfaction (variable Y). A total of 91 respondents were selected through purposive sampling among regular road users. Data were analyzed using validity testing, reliability testing, and simple linear regression. The validity test showed corrected item–total correlation values ranging from 0.608 to 0.854, all exceeding the r-table value of 0.207, indicating validity. The reliability test produced a Cronbach’s Alpha of 0.890 for variable X and 0.604 for variable Y, indicating acceptable internal consistency. Regression analysis yielded the equation Y = 29.115 – 0.715X + e, with a correlation coefficient R = 0.673 and a coefficient of determination R² = 0.453; the significance value p = 0.000 (<0.05) indicated a significant negative effect. The study highlights the importance of regular maintenance and prioritized repairs to improve road service quality and user satisfaction. The findings provide empirical evidence for policymaking in road maintenance budgeting, repair prioritization, public safety awareness, and periodic evaluation of maintenance programs.